Research Hotspots and Trends in Ciliopathies: A Bibliometric and Visualization Analysis. - Dong, Qian; Zhu, Jinhao; Liu, Jiang; Xu, Huan; Wesley, Hannah (BioMed Research International, 2026)
Purpose: This study conducted a comprehensive bibliometric analysis of research hotspots and development trends in ciliopathies to provide an overview of the global research landscape. Methods: The study retrieved relevant literature on ciliopathies from the Web of Science Core Collection up to July 27, 2024. Using the CiteSpace visualization software, co‐occurrence network analyses were performed on the authors, institutions, and keywords of the literature. Results: A total of 1821 papers were included, demonstrating a wave‐like increasing trend in annual publication volume. Among English‐language publications, Omran, Heymut had the highest number of articles. The cooperation network among the United States, the United Kingdom, and China was broader than that of other countries or regions. Omran, Heymut had the highest number of publications (64), placing him among the most prolific authors (defined as ≥ 60 publications); Knowles, Michael R. (58) and Leigh, Margaret W. (51) ranked second and third, respectively. Research hotspots mainly focused on functional mutations, congenital heart disease, cystic fibrosis, dyskinesia, primary ciliary dyskinesia, and genetics. Current ongoing hotspots include genetics, dynein, multiple morphological abnormalities, motile cilia, male infertility, variants, and sperm flagella. Conclusion: This study delineates the evolutionary trajectory of research themes, identifies established and emerging hotspots, and maps the global collaborative network. These findings provide a systematic, evidence‐based framework to guide future research directions, foster cross‐disciplinary collaboration, and optimize resource allocation in the ciliopathy field.